2010
DOI: 10.1186/1471-2407-10-220
|View full text |Cite
|
Sign up to set email alerts
|

The number and microlocalization of tumor-associated immune cells are associated with patient's survival time in non-small cell lung cancer

Abstract: BackgroundTumor microenvironment is composed of tumor cells, fibroblasts, endothelial cells, and infiltrating immune cells. Tumor-associated immune cells may inhibit or promote tumor growth and progression. This study was conducted to determine whether the number and microlocalization of macrophages, mature dendritic cells and cytotoxic T cells in non-small cell lung cancer are associated with patient's survival time.MethodsNinety-nine patients with non-small cell lung cancer (NSCLC) were included in this retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 27 publications
(27 reference statements)
8
102
1
Order By: Relevance
“…It has been previously shown that bronchial adenocarcinoma is characterized by aggressive development and poor prognosis compared to other histologic types of NSCLC (Cooke et al, 2010;Maeda et al, 2011;Tomaszek et al, 2011). This behavior may be attributed to the properties of the tumor itself, as well as to impaired anti-tumor immune response (Dai et al, 2010;Watanabe et al, 2011). Tryptofan degradation along the kynurenine pathway has been shown to be a major factor contributing to escape of tumor cells from immune surveillance (Munn et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that bronchial adenocarcinoma is characterized by aggressive development and poor prognosis compared to other histologic types of NSCLC (Cooke et al, 2010;Maeda et al, 2011;Tomaszek et al, 2011). This behavior may be attributed to the properties of the tumor itself, as well as to impaired anti-tumor immune response (Dai et al, 2010;Watanabe et al, 2011). Tryptofan degradation along the kynurenine pathway has been shown to be a major factor contributing to escape of tumor cells from immune surveillance (Munn et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Overall invasiveness of malignant tumors is dependent on the properties of the tumor at the molecular level (Watanabe et al, 2011), as well as on the proper response of the immune system (Dai et al, 2010 tumors, including lung cancer, may be attributed to metabolites of tryptophan degradation via kynurenine pathway (Munn and Mellor, 2007;Suzuki et al, 2010). It is the main pathway for tryptophan metabolism catalyzed by indoleamine 2,3-dioxygenase (IDO) and kynurenine aminotransferases (KATs), resulting in synthesis of kynurenic acid (KYNA) (Figure 1) (Fulop et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to examine the prognostic significance of the ALC/ AMC ratio at diagnosis and its relationship with TAMs in lesional tissues in patients with cHL, two parameters that reflect the tumor microenvironment and host immunity. Peripheral monocytosis has been associated with a poor prognosis in patients with lymphomas as well as those with solid tumors [21][22][23]. Myeloid-lineage cells may promote tumorigenesis through immunosuppression and the promotion of the tumor vasculature required for tumor growth and progression [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…108 Certain cell types in this infiltrate correlated with patient prognosis, including macrophages and lymphocytes, suggesting an important role in lung cancer pathogenesis. 109 In a syngeneic mouse model, lung cancer growth was reduced by restricting 'alternative' macrophage activation. 110 Research defining pathways that regulate lung cancer inflammation may reveal new targets for therapy.…”
Section: Lung Cancer and Inflammationmentioning
confidence: 99%